Flexible whispering gallery mode optical microcavities for lasers and sensors - Ta, Van Duong (2014)
Optical microresonators or microcavities confine light to tiny volumes known as optical modes where the light-matter interactions are strongly enhanced. They are basic building blocks for the investigation of cavity quantum electrodynamics, nonlinear optical effects, and employed as optical switches, optical filters, lasers and sensors. Among different geometries, whispering gallery mode (WGM) cavities, working based on total internal reflection, are alternative structures for realization of low threshold lasers and sensitive sensors thanks to their intrinsically small mode volume and high quality (Q) factor. Up to date, most high Q factor WGM resonators rely on semiconductor techniques requiring costly apparatuses and a number of complex processes. This conventional approach has some limitations: high cost, difficulty for doping gain medium into the cavities and mechanical inflexibility. Therefore, exploiting soft matter that suppresses the above limitations of semiconductor technology is a significant task. In this thesis, we demonstrate our successful exploration of novel soft matter compositions for surface tension-induced high Q factor WGM cavities namely polymer droplets, hemispheres and microfibers. Because the structures are self-assembled, the fabrication is relatively simple. By incorporating organic dye molecules into these structures, lasing with excellent performances such as narrow spectral linewidth, well-defined polarization, clear mode spacing, and strong photostability have been observed under optical excitation. Single mode operation, being important for on-chip applications and optical integrated circuits, is achievable from the three configurations. Especially interesting, the hemisphere and fiber lasers can be used for refractive index sensing for gases and liquids. Complex structures like coupled fiber lasers are also studied for robust single mode operation and improving the sensor’s sensitivity. This achievement indicates a full possibility to integrate between fiber cavities or fiber cavity with fiber waveguide, enabling potential applications of polymer fibers for flexible optical integrated devices. Compared with the traditional semiconductor or inorganic resonators, our cavities have many advantages including low production cost, mechanical flexibility and being straightforward for doping functional materials such as organic molecules or semiconductor nanomaterials. Furthermore, we successfully employ the hemispherical resonators to realize colloidal quantum dot lasing. This new kind of laser is considered as future coherent light source due to their photo/temperature stability and color tunability. The result opens a prospect of using the hemispheres as template cavities for realization of various microlasers based on different gain mediums such as nanocrystal nano/microwires and organic semiconductors. In conclusion, we have contributed promising material compositions and straightforward techniques for creating flexible high Q factor cavities with promising applications as bendable/stretchable microlasers and sensors. Our finding should be also useful for investigation of novel optical nonlinear effects and active/passive components in optical plastic devices/circuits.